Implementation of Sustainable Tourism at Ketapang Beach Lampung - Ni Made Ayu Windu Kartika; I Gede Mudana (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: This study aims to analyze the implementation of sustainable tourism in the operation of Ketapang Beach (Pantai Ketapang) in Lampung, Sumatra. Research methods: It is a descriptive, qualitative research. The data was collected by direct observation, document study, and literature studies from related journals. Results and discussion: Ketapang Beach requires development that involves all tourism stakeholders because it has much potential to be developed but has not been planned and realized correctly. Implication: This study explains the potential possessed by Ketapang Beach through a SWOT analysis and provides a sustainable tourism model design for the tourist attraction of Ketapang Beach. Keywords: beach, sustainable tourism, model.